Pengembangan Modul Berbasis Strategi REACT (Relating, Experiencing, Applying, Cooperating, and Transfering) Berbantuan Flipbook Maker Pada Materi Bangun Datar Kelas VII SMPN 2 Turatea - Nurul Fatimah; Andi Kusumayanti; Nursalam; Andi Ika Prasasti Abrar (Alauddin Journal of Mathematics Education, 2023)
This study aims to determine the process and results of module development based on the REACT strategy assisted by flipbook makers on class VII flat construction material that is valid, practical, and effective so that it is feasible to use. This type of research is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The results showed that the validity criteria based on the validation results by the validator team was 3.68 in the "very valid" category. The practicality criteria were obtained based on the results of the questionnaire analysis of the teacher's response to the module by 91% in the "very positive" category and the observation of the teacher's ability to manage learning was 4.53 in the "good" category. From the two analysis results, the REACT strategy-based module met the practicality criteria. The results of the effectiveness criteria were obtained based on the results of the student response questionnaire analysis of 89.8% in the "very positive" category, observation of student activity during the learning process by 82% in the "very good" category, and the learning achievement test obtained completeness of 89%. so that the measurement results for effectiveness criteria are met. Thus it can be concluded that the REACT strategy-based module using the flipbook maker is feasible to be applied in the learning process.